FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT INVESTASI DI PASAR MODAL SYARIAH PADA MAHASISWA FEBI IAIN FATTAHUL MULUK PAPUA - Rani Nur Indah Lestari; Miftahul Huda; Abdul Karman (OIKONOMIKA: Jurnal Kajian Ekonomi dan Keuangan Syariah, 2020)
This study aims to determine the factors that influence the intention of investment namely the encouragement from within individuals, social motive, and emotional factor partially and simultaneously on the intention of students’ investment in Islamic capital markets. This research method is quantitative. The population in this study is students of Islamic Economics and Business Faculty in IAIN Fattahul Muluk Papua which consisted of Islamic economics and Islamic banking study programs from 2016 to 2019. The sample in this study is 76 students. The sampling technique uses simple random sampling. Data collection in this study uses the questionnaire method. Data analysis techniques used in this study is multiple linear regression using SPSS 16.0 application. The results of this study indicate that: (1) Encouragement from within the individual has a significant effect on the intention of investment, with a significance value of 0,000. (2) Social motive significantly influence the intention of investment, with a significance value of 0,000. (3) Emotional factor do not significantly influence the intention of investment, with a significance value of 0.168. (4) Encouragement from within individuals, social motive, and emotional factor simultaneously influence the intention of investment of Islamic Economics and Business Faculty students in IAIN Fattahul Muluk Papua.